2012
DOI: 10.1111/fwb.12016
|View full text |Cite
|
Sign up to set email alerts
|

Regional species richness, hydrological characteristics and the local species richness of assemblages of North American stream fishes

Abstract: Summary 1. Local assemblage structure, from a deterministic perspective, is presumably dictated by the regional species pool as well as regulated by local factors. We examined the relationships of the regional species pool and local hydrological characteristics to local species richness of North American freshwater fishes using data sets collected during the National Water Quality Assessment program conducted by the United States Geological Survey. 2. We predicted that local species richness is ultimately cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 57 publications
(109 reference statements)
1
27
2
Order By: Relevance
“…However, flow variability (CV) was an important predictor of variation in species richness only for Centrarchidae and Cyprinidae, with opposite impacts on species richness in each group. These results, particularly related to flow variability, confirmed the need to recognize the importance of differential taxonomic responses to environmental variability (Chinnayakanahalli et al , ; Knouft and Page, ; Niu et al , ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, flow variability (CV) was an important predictor of variation in species richness only for Centrarchidae and Cyprinidae, with opposite impacts on species richness in each group. These results, particularly related to flow variability, confirmed the need to recognize the importance of differential taxonomic responses to environmental variability (Chinnayakanahalli et al , ; Knouft and Page, ; Niu et al , ).…”
Section: Discussionsupporting
confidence: 64%
“…Increases in flow can increase stream connectivity and create larger and more stable habitats for fishes (Schlosser, ), whereas increases in flow variability can have varying effects on species richness depending on the degree of flow variability and individual species' tolerance to this variation (Niu et al , ). Species richness was positively correlated with flow in all analyses (all species, Centrarchidae, Cyprinidae, and Percidae).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive correlation between flow variability and fish species richness was consistent with patterns reported for Cyprinidae in North American (Niu et al, ). A trait based framework demonstrated that natural flow variability favors species exhibiting opportunistic and equilibrium life history strategies (Winemiller, ; Mims and Olden, ).…”
Section: Discussionmentioning
confidence: 99%
“…This time span permits estimation of biologically relevant hydrologic indices such as inter‐year coefficient of variation and mean rising rate of high flow events, and is comparable to the life spans of most fish species in the region (Pflieger, ). Nine hydrologic indices were calculated to characterize flow variability at each sampling site using the Indicators of Hydrologic Alteration software (IHA; The Nature Conservancy, ; as used in Niu et al, ; see Appendix SII).…”
Section: Methodsmentioning
confidence: 99%